POST-COVID-19 IMPAIRMENTS OF BONE METABOLISM IN PATIENTS WITH LONG BONE FRACTURES - Badriddinov Akobir Sadriddinovich; Khamdamov Bakhtiyor Zaripovich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation Vitamin D plays a central role in calcium homeostasis and bone matrix mineralization. Post-COVID-19 patients often develop vitamin D deficiency, which may impair bone healing. Understanding the biochemical changes in such patients is essential for optimizing fracture management. This article provides scientific research information about post-COVID-19 impairments of bone metabolism in patients with long bone fractures.